Phloem restriction of viroids in three citrus hosts is overcome by grafting with Etrog citron: potential involvement of a translocatable factor - Bani Hashemian, Seyed M.; Pensabene-Bellavia, Giovanni; Durán-Vila, Núria; Serra, Pedro (2017)
Viroid systemic spread involves cell-to-cell movement from initially infected cells via plasmodesmata, long-distance movement within the phloem and again cell-to-cell movement to invade distal tissues including the mesophyll. Citrus exocortis viroid (CEVd), hop stunt viroid, citrus bent leaf viroid, citrus dwarfing viroid, citrus bark cracking viroid and citrus viroid V remained phloem restricted when singly infecting Citrus karna, Citrus aurantium and Poncirus trifoliata, but not Etrog citron, where they were additionally detected in mesophyll protoplasts. However, when CEVd-infected C. karna was side-grafted with Etrog citron with the resulting plants being composed of a C. karna stock and an Etrog citron branch the viroid was detected in mesophyll protoplasts of the former, thus indicating that the ability of Etrog citron to support viroid invasion of non-vascular tissues was transferred to the stock. Further results suggest that a translocatable factor from Etrog citron mediates this viroid trafficking.